Gender Differences in Executive Compensation on British Corporate Boards - Al-Shaer, Habiba (2020)
We exploit the effectiveness of the Davies Report (2011), which urged FTSE 350 companies to increase female representation on corporate boards to examine the potential effect that this may have on the gender pay differential at the executive level. To this end, we employ a multivariate regression and a difference-in-differences approach that compare executive compensation between all-male executive boards and boards with at least one female executive. Using a sample of FTSE 350 companies that spans the period 2008-2015, we find that the differential executive compensation exists in bonus and equity compensation following the Davies Report (2011). Given that the differential compensation exists in the components that are primarily determined by the firm’s reported earnings and that female directors are prone to exhibit higher conditional conservatism in their financial reporting, we examine whether the firm’s financial reporting practice plays a role in determining the differential executive compensation. Our investigation reveals that the presence of female executive directors on board makes the effect of conditional conservatism more prominent, resulting in lower bonus and equity-based compensation.